Elections and the Timing of Devaluations - Ernesto H. Stein; Jorge M. Streb (Inter-American Development Bank, Office of the Chief Economist, 1999)
This paper presents a rational political budget cycle model for an open economy, in which devaluations are delayed in the pre-election period so as to increase the electoral chances of the party in office. By concentrating on closed economies, previous political cycle models had overlooked the influence of elections on the behavior of exchange rates. Voter uncertainty is introduced in two different dimensions. Not only are voters uncertain regarding the competency of the incumbent, but tey also ignore the degree to which the incumbent is opportunistic.
Keywords: 330; Abwertung; Wahl; Ökonomische Theorie der Demokratie; Unvollkommene Information; Offene Volkswirtschaft; Schätzung; Theorie